Content Analysis of Clarin Hayes' Personal Branding as a Doctor on Youtube: Analisis Isi Personal Branding Clarin Hayes Sebagai Dokter Di Youtube - Rachmadita, Kartika Alfi; Febriana, Poppy (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to find out how Clarin Hayes forms her personal branding on YouTube. This type of research is qualitative with a descriptive content analysis approach used by the researcher, which is content analysis from the point of view of Riffe, Lacy, and Fico (1998) in the youtube video of Clarin Hayes. The results show that Clarin Hayes is trying to establish personal branding as a doctor who can answer people's uncertainties through videos made with various discussions and have characteristics and Clarin Hayes is enough to prove that the personal branding that was formed was successfully carried out by Clarin Hayes.